Carrier lifetime and spin relaxation time study for electrical spin injection into GaAs - Oh, Eunsoon; Lee, T. K.; Park, J. H.; Choi, J. H.; Park, Y. J.; Shin, K. H.; Kim, K. Y. (AMER INST PHYSICS, 2009)
We fabricated spin light emitting diodes using oxide tunneling barriers between ferromagnetic materials (Ni0.8Fe0.2/Co0.9Fe0.1) and semiconductors (GaAs) and investigated the temperature-dependent carrier lifetime and spin relaxation time of the active GaAs layer. We observed the circular polarization of the free exciton from the electroluminescence spectra due to the spin injection from the ferromagnetic material, whereas the circular polarization of the conduction band to acceptor transition was negligible. From the temperature-dependent carrier lifetime and spin relaxation time of the active GaAs layer, we found that the spin injection efficiency was larger than 25% between 20 and 180 K, where the magnetic field dependence of the spin lifetime was ignored. 0 2009 American Institute of Physics. [DOI: 10.1063/1.3186026]
Keywords: QUANTUM-WELLS; HETEROSTRUCTURE; SEMICONDUCTOR